Why Students Do Not Engage in Contract Cheating - Rundle, Kiata; Curtis, Guy J.; Clare, Joseph (Frontiers in Psychology, 2019)
Contract cheating refers to students paying a third party to complete university assessments for them. Although opportunities for comercial contract cheating are widely available in the form of essay mills, only about 3% of students engage in this behaviour. This study examined the reasons why most students do not engage in contract cheating. Students (n = 1291) completed a survey on why they do not engage in contract cheating as well as measures of several individual differences, including self-control, grit and the Dark Triad traits. Motivation for learning and morality received the greatest endorsement for why students do not engage in contract cheating. Controlling for gender, individual differences predicted students’ reasons for not contract cheating. This study supports the use of criminological theories relating to self-control and opportunity to explain why students do not engage in contract cheating. Practically, this study may inform academic policies and assessment design that may reduce contract cheating.